How Are They Doing? Neurodevelopmental Outcomes at School Age of Children Born Following Assisted Reproductive Treatments. (March 2021) - Farhi, Adel; Glasser, Saralee; Gabis, Lidia V.; Hirsh-Yechezkel, Galit; Frank, Shay; Brinton, Louise; Scoccia, Bert; Ron-El, Raphael; Orvieto, Raoul; Lerner-Geva, Liat
Objective: The purpose of this study was to assess major neurodevelopmental aspects of children conceived by assisted reproductive treatments compared to spontaneously conceived children during the early school years. Material & Methods: In this follow-up study, mothers of 358 children born following assisted reproductive treatments and 401 spontaneously-conceived children were interviewed by telephone regarding their children's health and development, when the children were 7-8 years old. The main outcomes were maternal responses to 4 questionnaires: Developmental Coordination Disorder Questionnaire, Short Sensory Profile, Autism Spectrum Screening Questionnaire, and the Attention-deficit hyperactive disorder (ADHD) Child Symptom Inventory-4 subscale. Mothers reported diagnoses of ADHD and autism spectrum disorder. Results: No significant differences were found between the groups in Developmental Coordination Disorder Questionnaire or Short Sensory Profile scores upon univariate or multivariable analyses. There was a slightly higher but nonsignificant rate of diagnosed ADHD among children in the assisted reproductive treatment group (9.6% vs 5.5%; P = .18); on multivariable analysis, a nonsignificant increase in ADHD was also found for assisted reproductive treatment children (hazard ratio 1.45, 95% confidence interval 0.81-2.61). Regarding the Child Symptom Inventory-4 criteria for ADHD among the children who had never been diagnosed, there was also a slightly higher but nonsignificant rate among the assisted reproductive treatments compared to spontaneously-conceived children on univariate (2.4% vs 1.8%; P = .50) and multivariable analysis (odds ratio 0.88, 95% confidence interval 0.27-2.86). Autism spectrum disorder diagnosis or Autism Spectrum Screening Questionnaire scores were not significantly different; however, 5 of the 6 children with autism spectrum disorder diagnoses were in the assisted reproductive treatment group. Conclusions: Neurodevelopmental measures were similar in both groups, although nonconclusive regarding ADHD and autism spectrum disorder risk. These findings contribute to the knowledge regarding long-term assisted reproductive treatment outcomes.